Introduction – Here versus There: Beyond comparison in queer and sexuality politics. (January 2023) - Lalor, Kay; Browne, Kath
This special issue explores the simplification of common narratives that have developed in the wake of changing sexual and gender politics in the early part of the 21st Century into binarised narratives of a 'here' where sexual politics are 'sorted' and a 'there' which must 'catch up'. In this introduction, we reflect on the challenges of attending to the historical, material, political and legal forces that give 'here' and 'there' geopolitical, discursive and geographic coherence, and discuss how the papers in the special issue explore, challenge and contest the dynamics that underpin the construction of 'Here versus There'.